Operando Converting BiOCl into Bi2O2(CO3)xCly for Efficient Electrocatalytic Reduction of Carbon Dioxide to Formate - Fu, Huai Qin; Liu, Junxian; Bedford, Nicholas M.; Wang, Yun; Wright, Joshua; Liu, Peng Fei; Wen, Chun Fang; Wang, Liang; Yin, Huajie; Qi, Dongchen; Liu, Porun; Yang, Hua Gui; et al. (Nano-Micro Letters, 2022)
Bismuth-based materials (e.g., metallic, oxides and subcarbonate) are emerged as promising electrocatalysts for converting CO2 to formate. However, Bio-based electrocatalysts possess high overpotentials, while bismuth oxides and subcarbonate encounter stability issues. This work is designated to exemplify that the operando synthesis can be an effective means to enhance the stability of electrocatalysts under operando CO2RR conditions. A synthetic approach is developed to electrochemically convert BiOCl into Cl-containing subcarbonate (Bi2O2(CO3)xCly) under operando CO2RR conditions. The systematic operando spectroscopic studies depict that BiOCl is converted to Bi2O2(CO3)xCly via a cathodic potential-promoted anion-exchange process. The operando synthesized Bi2O2(CO3)xCly can tolerate − 1.0 V versus RHE, while for the wet-chemistry synthesized pure Bi2O2CO3, the formation of metallic Bio occurs at − 0.6 V versus RHE. At − 0.8 V versus RHE, Bi2O2(CO3)xCly can readily attain a FEHCOO- of 97.9%, much higher than that of the pure Bi2O2CO3 (81.3%). DFT calculations indicate that differing from the pure Bi2O2CO3-catalyzed CO2RR, where formate is formed via a *OCHO intermediate step that requires a high energy input energy of 2.69 eV to proceed, the formation of HCOO− over Bi2O2(CO3)xCly has proceeded via a *COOH intermediate step that only requires low energy input of 2.56 eV. Highlights: 1 An operando synthetic approach was exemplified to enhance catalyst stability for efficient reduction of CO2 to formate. 2 A highly stable Bi2O2(CO3)xCly electrocatalyst was synthesized by direct electrochemical conversion of BiOCl via a cathodic potential-promoted anion-exchange process under operando CO2RR conditions. 3 The surface Cl− in Bi2O2(CO3)xCly changes the p-orbital electron states to enhance the stability and alters the CO2RR pathway to markedly reduce the energy barrier.